"Ensuring The Sustainable Functioning And Sustainable Development Of The Transport Sector By Optimizing The Non-Core Assets Of Uty Jsc Republic Of Uzbekistan - Nodir Davurov Nizomovich (Genius Journals, 2022)
This article focuses on the operational planning and management of rail transport with the support of information systems. The sectoral and specific information systems present the major support for management decisions. Timeliness, accuracy and validity of the information has a significant share in decisions particularly in stochastic process that is transport. In field of Slovak Railways the infrastructure manager has built the Operating information system, which helps manage those decisions. A separate part of OIS consists Shift plan, which is the basic document for the operational management of traffic on the Slovak railways. It is important to note that the information systems decide on a particular real situation. Our paper deals the process for planning and managing the railway running with this OIS
Keywords: Operational information system; Infrastructure manager; Management